Performance Evaluation of Heterogeneous Network Based on RED and WRED - Wisam Mahmood Lafta; Saba Qasim Jabbar; Guangzhi Ma (Institute of Advanced Engineering and Science, 2016)
The developing of wireless networks becomes a very important issue nowadays, since it is considered as an easy-using tool without building new infrastructure to cover a wide working area. Applying TCP protocols with the application demands are implemented this work by considering heterogeneous environment of wireless networks connecting with wired networks. The TCP congestion is critical problem is faced heterogeneous environments, this problem is appeared through sending and receiving huge data from wireless networks to wired networks and vice versa. This work is proposed a new approach of using active queue management (AQM) technique with random early detection (RED) and weight random early detection (WRED) strategies to avoid the expected congestion between the heterogeneous environments. Our simulation results show that the quality of service (QoS) is improved by reducing the queue delay and buffer usage, and by increasing the average throughput and utilizationof the system. The simulation is carried out by using OPNET software to test the proposed models for different scenarios.